Pioneering laparoscopic surgery in South-eastern Nigeria - Ekwunife, Christopher; Chianakwana, Gabriel; Anyanwu, Stanley; Emegoakor, Chinemelum (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Nigeria lags behind in the deployment of laparoscopic surgical services, even among the developing countries. In spite of the huge abundant human and materials resources at its disposal, public hospitals are still underfunded. However, some tertiary health institutions in our sub-region have been able to brave the odds to modernize their services.Aim: To review the early experiences of two general surgery units in laparoscopic surgery at two institutions in South-eastern Nigeria.Materials and Methods: A 3-year retrospective analysis of the laparoscopic general surgery operations carried out in Nnamdi Azikiwe University Teaching Hospital, Nnewi, and Federal Medical Centre Owerri, Nigeria, was done.Results: A total of 20 cases have been done in both hospitals: 9 laparoscopic cholecystectomies, 10 laparoscopic appendectomies, and 1 laparoscopic liver abscess drainage. There was no conversion to open surgery. The average duration of postoperative stay after cholecystectomy and appendectomy were 2.1 and 1.5 days, respectively. There was no major complication despite the challenging intraoperative adverse conditions.Conclusion: Laparoscopic surgery is safe in our region, but its evolution is still slow in our centers. Improved surgeon training and subsidization of the costs of the procedures may hold the key for accelerated development.
Keywords: General surgery; laparoscopy; Nigeria